2018
DOI: 10.1111/bph.14215
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in targeting ion channels to treat chronic pain

Abstract: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…We then filtered only for clear-cut protein changing SNPs (missense mutations predicted deleterious by SIFT, nonsense mutations, splice site mutations, start codon mutations, and within-exon deletions and duplications), as such changes are potentially more amenable to function tests of pathogenicity; reducing from 18,106 SNPs prior to SIFT and pathogenicity analysis to 3,596 afterward. We then further filtered only for SNPs within ion channel genes, as members of this group of genes have already been implicated in Mendelian pain disorders, and testing techniques for ion channel function are well established; resulting in 28 SNPs ( Stevens and Stephens, 2018 ). For all SNPs, especially those whose rare allele frequency is < 5%, geographical and ethnic differences must be considered; rs140124801 has a rare allele frequency in EVS of 0.0051 (cohort size 6500), in gNOMAD Europeans = 0.0072 (cohort size 18,878), 1000 Genomes = 0.0048 (cohort size 2,504), and our population were Caucasian and predominantly born in the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…We then filtered only for clear-cut protein changing SNPs (missense mutations predicted deleterious by SIFT, nonsense mutations, splice site mutations, start codon mutations, and within-exon deletions and duplications), as such changes are potentially more amenable to function tests of pathogenicity; reducing from 18,106 SNPs prior to SIFT and pathogenicity analysis to 3,596 afterward. We then further filtered only for SNPs within ion channel genes, as members of this group of genes have already been implicated in Mendelian pain disorders, and testing techniques for ion channel function are well established; resulting in 28 SNPs ( Stevens and Stephens, 2018 ). For all SNPs, especially those whose rare allele frequency is < 5%, geographical and ethnic differences must be considered; rs140124801 has a rare allele frequency in EVS of 0.0051 (cohort size 6500), in gNOMAD Europeans = 0.0072 (cohort size 18,878), 1000 Genomes = 0.0048 (cohort size 2,504), and our population were Caucasian and predominantly born in the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic pain is considered as a major issue that affects the overall life quality of patient. Approximately, ~1.5 billion people are suffering with this condition globally [68] . Recently, a mouse model expressing N-type Ca v 2.2 VGCCs at the plasma membrane of peripheral somatosensory neurons via α2δ-1 accessory subunit revealed the role of these channels in pain modulation [69] , suggesting that Ca v 2.2 Ca 2+ channel may prove to be a potential drug target for novel analgesic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Kim H W et al proposed that 1 Hz electroacupuncture suppressed carrageenan-induced paw inflammation via sympathetic post-ganglionic neurons, while inflammation was restrained by 120 Hz EA in connection with the sympathoadrenal medullary axis [31]. Recently, increasing evidence has shown that the analgesic effect of EA is closely related to its regulation of ion channels in sensory neurons [32,33]. Particularly, increased attention has been paid to P2X3, which has been regarded as a potential target of inflammatory pain and neuropathic pain [34,35].…”
Section: Discussionmentioning
confidence: 99%